Networks : being a part and apart. - Behrendt, Larissa (JSTOR DDA Collection, 2022)
Our world is built around the people, groups and communities we surround ourselves with. They form networks of connections, beliefs and ideas that can help to shape the people we become. These networks have become vital in a time where lockdowns have pushed us apart, and reinforced the need to be a part of something whole. This anthology examines the ways we find joy in lockdown, keep people and places alive through memory, and search for connection in an increasingly digital age. Featuring poetry, short stories and visual art, it introduces bold new voices that will command your attention and prompt you to think differently about the relationships that make everyday life worthwhile.